The Effectiveness of Student Worksheet (Project-Based Learning) Based on The Values of Islamic Boarding School for The Biotechnology Subject to Train High School Students with Bioentrepreneuship Skills - Rukmana, Rinaldiyanti; Susantini, Endang; Bashri, Ahmad (Universitas Negeri Surabaya, 2020)
This study aimed at describing the effectiveness of student worksheet with an approach of project-based learning for the conventional biotechnology subject to train high school students with bioentrepreneurship skills. This study used instructional development method initiated by Fenrich through several steps: analysis, planning, designing, developing, implementation, evaluation, and revision. The experiment was conducted to 20 students at the twelfth grade in the Islamic Boarding School of A. Wahid Hasyim Jombang. The effectiveness of the project-based learning was 9.7% out of 100%. Students’ response was 90.0% on the values of Islamic boarding school or pesantren which become the indicator of having the bioentrepreneuship skills based on the summary of Adabul ‘Alim Wal Muta’allim kitab (hard work, responsibility, tolerance/tasamuh). Also, the completion of entrepreneurship project was 89.55%. These results show that the student worksheet is effective.